2011
DOI: 10.1136/thoraxjnl-2011-201054c.207
|View full text |Cite
|
Sign up to set email alerts
|

P207 Does the Nijmegen correlate to the D12 when used as an outcome measure in patients with breathing pattern dysfunction

Abstract: attended a screening visit; 58/129 screen failed (eg, due to deterioration in peak flow, unable to wean off regular asthma medications) leaving 71 randomised (2.5%) of total patients invited. Trial 2: similar picture, completed July 2011, extended by 6 months due to slow recruitment. Target to randomise ¼80, target to complete ¼68. Actual completed: 71/8398 (<1%) of those invited. Conclusion Achieving the completion target in randomised controlled trials requires significant administrative support, and the cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another small study showed a similar improvement over 24 months in both the Nijmegen questionnaire and HADS, but no correlation between the two scores [38]. A further study showed improvement in both the Nijmegen questionnaire and dyspnoea-12 scores post-retraining [39].…”
Section: Treatmentmentioning
confidence: 77%
“…Another small study showed a similar improvement over 24 months in both the Nijmegen questionnaire and HADS, but no correlation between the two scores [38]. A further study showed improvement in both the Nijmegen questionnaire and dyspnoea-12 scores post-retraining [39].…”
Section: Treatmentmentioning
confidence: 77%
“…NQ’s measurement properties have gained much attention due to its long record and frequent use in DB assessment, notably in conditions including bronchial asthma and hyperventilation syndrome 39 42. The available evidence indicated that the NQ had been evaluated using rigorous methods, and its content validity, internal consistency and reliability were commonly reported.…”
Section: Discussionmentioning
confidence: 99%